Impressões de um dirigente: Relatos e relatórios da Colônia Militar de Foz do Iguaçu nos anos de 1897-1898 (Revista de História Regional, 2008)
This article is constructed by the transcript of twodocuments relating to the installation of the Military Colonyin Fóz do Iguaçu, in the triple border region of Brazil - Paraguay- Argentina. The installation of this military venturerepresents, in all the political and governmental strategies ofthe Empire, one of the milestones of the integration of regionalborders in Brazil. The documentation consists of two annualreports, which were prepared, respectively, in the years 1897and 1898, by Joaquim de Salles human Torres, administratorof the Colony, designated in1897, by the Office of the thenState Minister of War, in the capital of the Empire. Thisdocumentary corpus is significant to the extent that theinformation contained therein enables the immertion in auniverse of personal impressions and new knowledge aboutthis region of international borders. As the historiographicproduction in Paraná crystallized knowledge about this militaryventure, for the privilege of certain sources, our intention isto socialize the contents of the two annual reports, enablingnew readings on the Military Colony of Foz do Iguacu.